Calculation of parameter of Ashcroft’s potential using vacancy formation energy for bcc metals like Cr, Mo, W, V, Nb, Ta, Tl, Eu and Zr - Ghorai, Amitava; Choudhury, Tirthankar; Das, Arjun; Dey, Rajesh; Ganguly, Sourav (Diffusion Fundamentals, 2012)
Variation of vacancy formation energy with the parameter of Ashcroft''s model for nine different exchange and correlation functions show almost similar nature for the bcc metals like Cr, Mo, W, V, Nb, Ta, Tl, Eu and Zr. The mean value of this parameter for these bcc metals are respectively 1.173, 1.383, 1.458, 1.263, 1.478, 1.489, 1.802, 2.222 atomic unit.